Conceptual Model of Informal Business Development Based on Intellectual Capital - Sumual, Tinneke Evie Meggy; Arham, Muhammad Amir; Kawulur, Arie; Rimbing, Rocky (Journal of International Conference Proceedings, 2021)
This paper aims to describe the conceptual model of informal business development applied to â€œTibo-Tiboâ€ fisherwomen in North Minahasa Regency. Data and information were obtained by observation and structured interviews to â€œTibo-Tiboâ€ fisherwomen, business partners and village governments. The data was analyzed qualitatively by using Miles Huberman perspective, through stages: data reduction, data presentation, conclusion drawing and verification. After going through the validity of experts, this paper produced a conceptual model of informal business development based on intellectual capital namely human capital, social capital and organizational capital. This paper recommends that through the intellectual capital approach "Tibo-Tibo" fisher women's business can be improved through empowerment. Empowerment in the form of human capital will increase the added value products with the availability of a variety of products for frozen food businesses and products for culinary businesses. Empowerment in the form of social capital will strengthen the values of relationships with business partners, trust to customers and employees and strengthen the work culture "mapalus" (local wisdom for the community) such as cooperation and helping each other. Empowerment in the form of organizational will strengthening the management and organizational professionalism as well as the acknowledgment of business license and product brands by consumers.